The relationship between Alexithymia and Psychological immunity among Students of the Faculty of Education at the University of Damascus - Al-Saqa, Sabah Mustafa Fathi; Nadar, Rand Mohammad Abdullah (Journal of Educational and Psychological Sciences, 2022)
The aim of the current research is to know the relationship between alexithymia and psychological immunity among students of the Faculty of Education at the University of Damascus. It also intended to explore gender and study year differences in the variables of alexithymia and psychological immunity. The research sample consisted of (377) male and female students. To achieve the goals of the study, the researcher used the alexithymia scale TAS-20, and prepared a psychological immunity scale. The results showed the results showed a negative correlation between alexithymia and psychological immunity, with the degree of correlation with Pearson's coefficient (-0.278), In addition there were statistically significant differences in favor of females and first-year students in alexithymia in the dimension of emotion recognition, no statistically significant differences appeared in the other two dimensions. As for the psychological immunity variable, there were no statistically significant differences according to the variable of gender and school year, also found that the research sample had an average level in alexithymia and psychological immunity. The research recommended a number of recommendations.
Keywords: alexithymia; psychological immunity; university students